Moving on From Sipuleucel-T: New Dendritic Cell Vaccine Strategies for Prostate Cancer - Sutherland, Sarah I. M.; Ju, Xinsheng; Horvath, L. G.; Clark, Georgina J. (Frontiers in Immunology, 2021)
Tumors evade the immune system though a myriad of mechanisms. Using checkpoint inhibitors to help reprime T cells to recognize tumor has had great success in malignancies including melanoma, lung and renal cell carcinoma (1-6). Many tumors including prostate cancer are resistant to such treatment (7). However, Sipuleucel-T, a dendritic cell (DC) based immunotherapy, improved overall survival (OS) in prostate cancer (8). Despite this initial success, further DC vaccines have failed to progress and there has been limited uptake of Sipuleucel-T in the clinic. We know in prostate cancer (PCa) that both the adaptive and the innate arms of the immune system contribute to the immunosuppressive environment. This is at least in part due to dysfunction of DC that play a crucial role in the initiation of an immune response (9). We also know that there is a paucity of DC in PCa (10), and that those there are immature, creating a tolerogenic environment (10-12). These attributes make PCa a good candidate for a DC based immunotherapy. Ultimately, the knowledge gained by much research into antigen processing and presentation needs to translate from bench to bedside. In this review we will analyze why newer vaccine strategies using monocyte derived DC (MoDC) have failed to deliver clinical benefit, particularly in PCa, and highlight the emerging antigen loading and presentation technologies such as nanoparticles, antibody-antigen conjugates and virus co-delivery systems that can be used to improve efficacy. Lastly, we will assess combination strategies that can help overcome the immunosuppressive microenvironment of PCa.